Ethno-Medicinal Importance of Some Invasive Plant Species Used by Tribal’s of Gadarwara Tehsil - Tamrakar, Ayushi; Soni, Rahul; Mohabe, Satish (Indian Forester, 2025)
The invasion of plants cannot be stopped from happening in the country. So why don’t we know their uses and take advantage of them. The tribal people have very good knowledge of the use of these invasive plants. According to the information received from them, they use 27 plants in medicinal purpose. Total 27 invasive plant species belonging to 24 genus & 16 families i.e. Asteraceae (6), Asclapidaceae (3), Solanaceae (3), Fabaceae (2), Euphorbiaceae (2), Papavaraceae (1), Cuscutaceae (1), Amaranthaceae (1), Cleomaceae (1), Pontederiaceae (1), Balsaminaceae (1), Convolvulaceae (1), Verbenaceae (1), Nyctaginaceae (1), Oxalidaceae (1) and Malvaceae (1) have been determined abundantly with inside the take a look at site. Five (5) parts following by Leaves, Stem, seed, Fruit and Root widely used as medicine. As per the data collected invasive plants are used to cure some diseases including fever, diarrhea, earache, rheumatism, asthma, hair fall, hair graying, leucoderma, cough, snake bite, jaundice diabetes, cancer, malaria and menstrual irregularities etc. The outcome of the one-year critical field survey on invasive plants in the different parts of Gadarwara Tehsil forest at various seasons.